EVALUATION OF POLISHING EFFICIENCY IN DIFFERENT REGIONS OF LITHIUM DISILICATE OVERLAYS THROUGH PROFILOMETRY SIMULATING CLINICAL CONDITIONS - Souza, Wuislane Lucia Ribeiro; de Moraes, Marcia Marie Maru; Kapps, Vanessa; Perez, Cesar dos Reis (ARACÊ, 2025)
This in vitro study evaluated the efficiency of polishing maneuvers on different areas of milled lithium disilicate overlays using contact profilometry, simulating clinical conditions. Six milled lithium disilicate overlays were fabricated using a computer-aided design (CAD) and computer-aided manufacturing (CAM) system. For each sample, three specific regions were selected: an external smooth slope (ES), an internal grinding slope (IS), and a proximal area between the marginal ridge and the proximal fossa (FO), and three different conditions were tested, namely: glazing, finishing, and polishing. The finishing system was composed of fine and ultrafine diamond points, and the polishing system used was rubber points. Contact profilometry enables the generation of a quantitative assessment through roughness profiles and a qualitative evaluation through three-dimensional (3D) images. The overlays’ average surface roughness (Ra) was assessed using a profilometer, 3D images were obtained using the Talymap software, and Ra data were compared using one-way analyses of variance (p<0.05). The results revealed that there were statistically significant differences between the dental area (p=0.049), surface treatment (p<0.00), and the interaction between the factors (p<0.00). Considering the treatment factor, statistically significant higher roughness was found in the polished FO group (p<0.05). The fossa is a non-flat region with high masticatory demand; its statistically significantly higher roughness for polishing allows us to assume that access to polishing instruments is limited in this region, preventing efficient action. Such finishing and polishing procedures are widely used in clinical practice and demand our attention regarding their effectiveness in the different areas of ceramic restoration.